ChemInform Abstract: Asymmetric Synthesis of α‐Amino Acids via Homologation of Ni(II) Complexes of Glycine Schiff Bases. Part 2. Aldol, Mannich Addition Reactions, Deracemization and (S) to (R) Interconversion of α‐Amino Acids. Issue 51 (17th December 2013) - Sorochinsky, Alexander E.; Acena, Jose Luis; Moriwaki, Hiroki; Sato, Tatsunori; Soloshonok, Vadim
Abstract Review: 61 refs.